A NARRATIVE REVIEW OF APIACEAE FAMILY PLANTS IN USADA NETRA FOR EYE DISEASE TREATMENT - Tirta, Luh Pande Putu; Yadnya Putra, A.A Gede Rai (Journal Pharmaceutical Science and Application, 2020)
Background: Eye health really needs to be maintained so as to avoid diseases such as red-eye (conjunctivitis) and stye (hordeolum). Conjunctivitis and hordeolum are caused by bacteria, and their treatment is generally using antibiotics. However, if antibiotics are used irrationally it can be dangerous to health, therefore at this time, people are more interested in traditional medicine. One of them is Balinese traditional medicine, Usada Netra. Usada Netra is a science that deals with the prevention, treatment and recovery of eye diseases. Objective: This review discusses conjunctivitis, hordeolum and its treatment, processing of herbs for eye diseases in Usada Netra, botanical aspects, phytochemical and pharmacological effects of three plant Apiaceae family based on the results of scientific research as well as the correlation with eye treatment in pharmaceutical sciences. Methods: Search data in this article review with the help of search engines namely Google Scholar, and online journal provider sites, including PubMed, Biomed, NCBI, and primary data obtained from international journals, national journals and usada Bali books that have been published. Result: Based on the pharmacological effects produced by the Apiaceae family plant can inhibit the growth of bacteria that cause conjunctivitis and hordeolum. Conclusion: The use of plant Apiaceae family can be recommended for treatment of the eye such as conjunctivitis and hordeolum, with due regard to the safety requirements for eye treatment preparations. Keywords: Antibacterial, Apiaceae Family, Conjunctivitis, Hordeolum